2017
DOI: 10.1038/s41598-017-15933-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-related intermediate band in P-rich GaNxPyAs1−x−y alloys

Abstract: The electronic band structure of phosphorus-rich GaNxPyAs1−x−y alloys (x ~ 0.025 and y ≥ 0.6) is studied experimentally using optical absorption, photomodulated transmission, contactless electroreflectance, and photoluminescence. It is shown that incorporation of a few percent of N atoms has a drastic effect on the electronic structure of the alloys. The change of the electronic band structure is very well described by the band anticrossing (BAC) model in which localized nitrogen states interact with the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…Moreover, Ga(PAsN) alloys with P concentration greater than 60% have also been studied [25][26][27][28] . This range of P concentration in Ga(PAsN) alloy seems to be the most interesting from the viewpoint of the intermediate band formation and the lattice matching with Si platform 28 . The possible integration of Ga(PAsN) with Si platform is a very important advantage of this alloy, which also makes this material system very interesting for laser applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Ga(PAsN) alloys with P concentration greater than 60% have also been studied [25][26][27][28] . This range of P concentration in Ga(PAsN) alloy seems to be the most interesting from the viewpoint of the intermediate band formation and the lattice matching with Si platform 28 . The possible integration of Ga(PAsN) with Si platform is a very important advantage of this alloy, which also makes this material system very interesting for laser applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore in recent years this alloy has been intensively explored [21][22][23][24] . Moreover, Ga(PAsN) alloys with P concentration greater than 60% have also been studied [25][26][27][28] . This range of P concentration in Ga(PAsN) alloy seems to be the most interesting from the viewpoint of the intermediate band formation and the lattice matching with Si platform 28 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the incorporation of N in GaP leads to an extremely large band-gap bowing and N-induced transformation from an indirect to a pseudo-direct band gap which consequently increases the emission intensity of the semiconductor. It was also previously shown that the incorporation of small content of N into P-rich GaPAs leads to the formation of intermediate band and the change of the nature of the fundamental band gap from indirect to direct [14]. The observed N-induced modification of the electronic band structure was also explained by the Band Anti Crossing (BAC) model.…”
Section: Introductionmentioning
confidence: 71%
“…The changes of band structure is usually described by this model that calculates the changes of band structure induced by isovalent N atom in a III-V host matrix . According to this model, the interaction of the localized N level with the states of the GaPAs or GaP host leads to the formation of E− and E+ bands in GaNP or GaPN alloy, respectively [14]. In addition, the observation of the isolated intermediate band offers a potential of using P-rich GaNPAs or GaP alloys for intermediate band solar cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the epitaxial growth of quasilattice-matched GaP on silicon (misfit of 0.37% at room temperature) has been developed for use as an efficient platform for the subsequent integration of low-defect or defect-free III-V-based heterostructures. For instance, the development of GaP/Si pseudo-substrates opens a route for the growth of direct-band-gap materials, using for example diluted nitride GaPN-based materials (Kunert et al, 2006;Ilahi et al, 2015;Yamane et al, 2017;Zelazna et al, 2017). Many strategies have been developed to suppress, reduce or filter the structural defects known to appear in such systems and detrimental for applications, such as dislocations (latticemismatch defects), micro-twins (MTs) (Devenyi et al, Lin et al, 2013;Lenz et al, 2019;Farin et al, 2019) resulting from the growth of polar crystals on non-polar substrates.…”
Section: Introductionmentioning
confidence: 99%